OD TRANZICIJE DO GLOBALIZACIJE: POLITIČKI (NE)IDENTITET(I) EUROPE - Banovikj-Markovska, Angelina (Odjel za kulturologiju Sveučilišta J. J. Strossmayera u Osijeku, Institut društvenih znanosti Ivo Pilar u Zagrebu, 2014)
It is evident that the final phase of European identity formation would happen in South-Eastern Europe, although for the majority of European citizens, it is still a rather empty, only mental idea. However, for their governments, it represents a minor “grey zone” related to pre-political consciousness which refuses to participate in a democratic search for European legitimacy. The mentioned project tries not only to (re)integrate the present political borders, but also to create a democratic public space which would stimulate the political and cultural promotion to create a new identity. The question raised is: Which way has European Union chosen to create its new, post national, civic or better to say, transnational political identity?
Keywords: politics; identity; Europe; transition; globalization